Modelling of Spacecraft Dynamics at Deployment of Large Elastic Structure. (22nd August 2012) - Khoroshilov, V. S.; Zakrzhevskii, A. E.
Abstract : In this paper, a new approach to the modelling of the deployment dynamics of a flexible multi-body system with the time dependent configurations is demonstrated in the frame of the study the dynamics of a spacecraft with the gyro-gravitational system of stabilization. Primarily the gravitational stabilizer that is made as a pantograph structure is in a compact form. The deployment of a flexible pantograph structure is performed after placing the spacecraft into orbit and completion of the preliminary damping by a special jet-propelled system, and after uncaging the gyros. After its deployment, the pantograph turns into an elongated structure that serves as a gravitational stabilizer and carrier of solar batteries. The objective of the study is the creation of the generalized mathematical model and the conducting of the computational modelling of the spacecraft dynamics. The equations of motion are derived with the use of the Eulerian-LaGrangian formalism and symbolic computing. Numerical simulations of the typical operational mode of the system are conducted taking into account various control profiles for the deployment. Numerical results indicate that the system used for attitude stabilization ensures the shape of the deployed design and prescribed accuracy of the orientation.